Immigrating into the Occupation: Russian-Speaking Women in Palestinian Societies. Issue 1 (November 2018) - Michaeli, Inna
Social researchers have extensively addressed the immigration of one million Russian speakers to Israel/Palestine over the past twenty-five years. However, the immigrants' incorporation into the Israeli occupation regime and the ongoing colonisation of Palestine have rarely been questioned as such. In the interviews informing this article, Russian-speaking immigrant women living in Arab-Palestinian communities discuss their complex relations with Palestinian, Jewish-Israeli and Russian-Israeli communities. Sharing a background with Russian-speaking Jewish Israelis on the one hand, and marital kinship ties to Palestinians on the other, these women encounter multiple boundaries of territory and identity in their everyday lives. Drawing on feminist border thinking, I explore these encounters as a navigation through geopolitical and epistemic borderlands in a dense colonial reality. I am particularly interested in the potential of such an exploration to question essentialism and destabilise binary ethno-national categories of identity, such as Arab/Jew and Israeli/Palestinian, that dominate not only hegemonic but also emancipatory discourses. These binary divisions are not a straightforward outcome of political regimes but rather the result of ongoing border-making processes, which are vulnerable to disorder and disruption. This perspective aims to enrich understandings of the roles that gendered ethno-national identities play in sustaining the colonial relations of power in Israel/Palestine.